Serotonin 5‐HT7 receptors require cyclin‐dependent kinase 5 to rescue hippocampal synaptic plasticity in a mouse model of Fragile X Syndrome. (6th May 2021) - Costa, Lara; Tempio, Alessandra; Lacivita, Enza; Leopoldo, Marcello; Ciranna, Lucia
Abstract: Fragile X Syndrome is a genetic form of intellectual disability associated with autism, epilepsy and mood disorders. Electrophysiology studies in Fmr1 knockout (KO) mice, a murine model of Fragile X Syndrome, have demonstrated alterations of synaptic plasticity, with exaggerated long‐term depression induced by activation of metabotropic glutamate receptors (mGluR‐LTD) in Fmr1 KO hippocampus. We have previously demonstrated that activation of serotonin 5‐HT7 receptors reverses mGluR‐LTD in the hippocampus of wild‐type and Fmr1 KO mice, thus correcting a synaptic dysfunction typically observed in this disease model. Here we show that pharmacological inhibition of cyclin‐dependent kinase 5 (Cdk5, a signaling molecule recently shown to be a modulator of brain synaptic plasticity) enhanced mGluR‐LTD in wild‐type hippocampal neurons, which became comparable to exaggerated mGluR‐LTD observed in Fmr1 KO neurons. Furthermore, Cdk5 inhibition prevented 5‐HT7 receptor‐mediated reversal of mGluR‐LTD both in wild‐type and in Fmr1 KO neurons. Our results show that Cdk5 modulates hippocampal synaptic plasticity. 5‐HT7 receptors require Cdk5 to modulate synaptic plasticity in wild‐type and rescue abnormal plasticity in Fmr1 KO neurons, pointing out Cdk5 as a possible novel target in Fragile X Syndrome. Abstract : Inhibition of Cdk5 in wild‐type mouse hippocampal neurons enhanced mGluR‐LTD, which became comparable to that observed in the Fmr1 KO mouse model of Fragile X Syndrome, suggesting that: (a) Cdk5 regulates mGluR‐LTD; (b) Cdk5 activity might be reduced in Fragile X Syndrome. Inhibition of Cdk5 abolished 5‐HT7 receptor‐mediated reversal of mGluR‐LTD in wild‐type and Fmr1 KO neurons, indicating that Cdk5 is involved in 5‐HT7 receptor‐mediated effect.